Effectiveness of the Online Learning Process and Work Engagement of Educators Due to Changes in Management Policy During the Covid-19 Pandemic: A Case Study of the Bina Ummah Foundation of Doctor Haji Adamri Al Husainy - Leni Rizqa Astuti; Hajan Hidayat (MID Publisher International, 2024)
The purpose of this study was to find out and explore information about how effective the online learning process is and how the work engagement of educators at the Bina Ummah Doktor Haji Adamri Al Husainy Foundation in Batam City during the covid-19 pandemic. This type of research uses a qualitative approach with a case study method. Informants or subjects in this study were MI and MTs educators, Chair of the Foundation, One Roof Management (MSA) staff and had worked for at least 2 years. Data collection techniques using semi-structured interview techniques. Researchers used data analysis described by Creswell. The results of this study indicate the goals and objectives of the Bina Ummah Foundation for education, social and religious or religion. During covid-19 the Foundation implemented a new policy, namely the online learning process using technology. The media used are Zoom, Whatsapp, Google Meet, and Youtube. This policy is considered less effective. This is due to obstacles such as no interaction so that students cannot understand, difficulties in delivering material, material is difficult for students to accept, lack of awareness of obligations. The advantages of this policy are having free time and increasing knowledge about technology. In addition, the drawbacks of this policy are a lot of time wasted, the learning process is not effective and the lack of awareness of responsibility to students. The level of work engagement is considered to have decreased from before, but it did not break the aspect of the work spirit or vigor of the educators. Aspects of dedication are given by educators by showing a sense of love for their work such as being responsible, committed, disciplined, obeying the rules and working sincerely and sincerely. Work engagement factors are the existence of trust, work contracts and the existence of reciprocal relationships that are accepted. Aspects of the preoccupation of work or absorption most of them feel more engrossed in working when face to face. disciplined, obeying the rules and working sincerely and sincerely. Work engagement factors are the existence of trust, work contracts and the existence of reciprocal relationships that are accepted. Aspects of the preoccupation of work or absorption most of them feel more engrossed in working when face to face. disciplined, obeying the rules and working sincerely and sincerely. Work engagement factors are the existence of trust, work contracts and the existence of reciprocal relationships that are accepted. Aspects of the preoccupation of workor absorption most of them feel more engrossed in working when face to face.